2013
DOI: 10.1007/s11481-013-9511-3
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Levels of Vesicular Trafficking Proteins Involved in HIV Replication in the Brains and CSF of Patients with HIV-associated Neurocognitive Disorders

Abstract: Human immunodeficiency virus (HIV) associated neurocognitive disorders (HAND) remain prevalent despite improved antiretroviral therapies. A HAND-specific biomarker indicative of neuropsychological impairment (NPI) would give insight into disease progression and aid clinicians in designing therapy. Endosomal sorting complex required for transport (ESCRT) proteins such as tumor susceptibility gene (TSG)-101, vacuolar protein sorting (VPS)-4 and LIP-5 are important for HIV replication and recently antiviral inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Numerous studies have addressed potential HIV-associated CSF biomarkers that may be used alone or in combination to either predict CNS disease severity or to predict the progression of HIV CNS disease [16-20]. Similarly, many studies have assessed changes in hpTau levels in CSF as a biomarker in AD, and more recently in HIV [21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have addressed potential HIV-associated CSF biomarkers that may be used alone or in combination to either predict CNS disease severity or to predict the progression of HIV CNS disease [16-20]. Similarly, many studies have assessed changes in hpTau levels in CSF as a biomarker in AD, and more recently in HIV [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, differences in the levels of autophagy markers between young and old HIV patients with encephalitis have been reported, with the former patients displaying an increase in BECLIN-1, CATHEPSIN D and LC3, whilst these proteins are reduced in the latter group compared to agematched HIV patients without encephalitis [80]. Of note, these differences correlate with the severity of neurodegenerative pathology.…”
Section: Autophagy Alterations In the Central Nervous System During Hmentioning
confidence: 99%
“…It is important to note that some of the effects of TAT on autophagy may be indirect, as it is also able to interfere with the endo-lysosomal compartment, by increasing luminal pH and compromising membrane integrity [84]. A recent detailed study of the effect of TAT on autophagy showed that treatments both in vitro and in GFAP-TAT transgenic mice induce accumulation of abnormal neuronal autophagosomes, suggesting that TAT alters the fusion of autophagosomes with lysosomes [80]. It is interesting that TAT was found in association with the lysosomal protein LAMP2A.…”
Section: Autophagy Alterations In the Central Nervous System During Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have shown that HIV-1 proteins might trigger neurodegeneration by interfering with clearance pathways such as macroautophagy (Alirezaei et al , 2008a; Alirezaei et al , 2008b; Zhou et al , 2011), a pathway necessary for recycling proteins or defective and older intracellular organelles (Cuervo, 2004). These alterations in autophagy in HIV-1 patients and transgenic (tg) mice are exacerbated with age (Fields et al , 2013a). Moreover, HIV-1 Tat (trans-activator of transcription) could either activate or suppress, depending on the conditions, autophagy function in glial cells (Bruno et al , 2014), macrophages (Wang et al , 2011) and bystander monocytes (Schenk et al , 2011), and Tat triggers neurodegeneration by disrupting endolysosomal functioning (Hui et al , 2012).…”
Section: Introductionmentioning
confidence: 99%